The effect of natural products on head lice: In vitro tests and clinical evidence - Heukelbach, Jorg; Canyon, Deon; Speare, Rick (Journal of Pediatric Infectious Diseases, 2007)
The therapy of pediculosis remains a common problem in pediatric clinical practice. As resistance to commonly used chemical pediculicides, such as permethrin, is constantly increasing, there is a need for the development of new compounds that are effective in causing mortality in adult lice and their eggs. Natural products have been used in traditional medicine for thousands of years and recently have been of increasing interest, since the costs are usually lower and they are considered less toxic by the public. Here we present a review on plant compounds used for the treatment of head lice. An overview is given on published evidence on the use of natural product pediculicides and ovicides in clinical trials and in vitro studies. We conclude that several plant products offer promise for new compounds to treat head lice infestation. However, the number of clinical studies is very limited, and there is an urgent need to increase research assessing the effectiveness and safety of promising compounds. Over the counter natural products should be supported by in vitro data and by adequately designed comparative trials that evaluate cure rates and safety.
Keywords: Head lice; pediculosis; natural product; essential oil; efficacy; therapy